The effect of undernutrition on sputum culture conversion and treatment outcomes among people with multidrug-resistant tuberculosis: a systematic review and meta-analysis - Fasil Wagnew; Kefyalew Addis Alene; Matthew Kelly; Darren Gray (International Journal of Infectious Diseases, 2023)
Objectives: We aimed to evaluate the effect of undernutrition on sputum culture conversion and treatment outcomes among people with multidrug-resistant tuberculosis (MDR-TB). Methods: We searched for publications in the Medline, Embase, Scopus, and Web of Science databases. We conducted a random-effect meta-analysis to estimate the effects of undernutrition on sputum culture conversion and treatment outcomes. Hazard ratio (HR) for sputum culture conversion and odds ratio (OR) for end-of-treatment outcomes, with 95% CI, were used to summarize the effect estimates. Potential publication bias was checked using funnel plots and Egger's tests. Results: Of the 2358 records screened, 63 studies comprising a total of 31,583 people with MDR-TB were included. Undernutrition was significantly associated with a longer time to sputum culture conversion (HR 0.7, 95% CI 0.6-0.9, I2 = 67·1%), and a higher rate of mortality (OR 2.8, 95% CI 2.1-3.6, I2 = 21%) and unsuccessful treatment outcomes (OR 1.8, 95% CI 1.5-2.1, I2 = 70%). There was no significant publication bias in the included studies. Conclusion: Undernutrition was significantly associated with unsuccessful treatment outcomes, including mortality and longer time to sputum culture conversion among people with MDR-TB. These findings have implications for supporting targeted nutritional interventions alongside standardized TB drugs.